2010
DOI: 10.4314/pamj.v2i1.51706
|View full text |Cite
|
Sign up to set email alerts
|

Eclampsia and seasonal variation in the tropics - a study in Nigeria

Abstract: Background:A retrospective observational study on the seasonal variation in the admission of eclampsia patients to the multi-disciplinary intensive care unit (ICU) of National Hospital, Abuja, Nigeria over a five-year span (March 2000 – March 2005) was carried out.Method:The patient’s case files and ICU records were used to extract the needed data. The diagnosis of eclampsia was based on clinical and laboratory findings by the obstetricians.Results:There were a total of 5,987 deliveries during the study period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 22 publications
1
22
1
2
Order By: Relevance
“…Raised LDH level is known to be associated with HELLP syndrome, DIC and also heart disease, thus long term follow up of these young women for cardiac diseases like myocarditis, myocardial infarction, ect, is necessary. 8 There was no association between seasonal variation and occurrence of the disease observed in this study as opposed to a study by Magnus et al, in which there was a peak in occurrence of preeclampsia during winter.…”
Section: Discussioncontrasting
confidence: 56%
“…Raised LDH level is known to be associated with HELLP syndrome, DIC and also heart disease, thus long term follow up of these young women for cardiac diseases like myocarditis, myocardial infarction, ect, is necessary. 8 There was no association between seasonal variation and occurrence of the disease observed in this study as opposed to a study by Magnus et al, in which there was a peak in occurrence of preeclampsia during winter.…”
Section: Discussioncontrasting
confidence: 56%
“…Thirteen of the studies found a statistically significant relationship between season and temperature on maternal outcomes. Some studies did not examine statistical significance entirely or measure the significance between maternal outcomes and seasonal variation (Bondevik et al, 2000;Hammerich et al, 2002;Crowther, 1985;Okafor et al, 2009;Halimi et al, 2010), while other studies found no statistical significance (Jamelle, 1998;Wacker et al, 1998;Soroori et al, 2007). It is important to note that seasonal patterns differ between countries based on climatology (e.g.…”
Section: Seasonalitymentioning
confidence: 94%
“…Contrarily, Immink et al (2008) found a significant correlation (p o0.032) in Tygerberg, South Africa, between the number of patients admitted with pre-eclampsia and low minimum temperatures; June had the lowest temperature of 7 1C compared to a maximum of 16.3 1C in February. Okafor et al (2009) documented a significant number of women admitted during the rainy seasons and suggested a link between the seasonality of eclampsia to the seasonality of malaria. This was confirmed in Anya's (2004) research, which established a 5.4 fold increase in eclampsia (p ¼0.008) during the malarial season.…”
Section: Seasonality Of (Pre-) Eclampsiamentioning
confidence: 96%
See 2 more Smart Citations